Analisis kelayakan usaha ekspor ikan (studi kasus PT. Hui Mei Wei Aquatic Product Trading) di Kota Kendari, Sulawesi Tenggara - Usman, Rahmad Nuzul; Budiyanto; Mansyur, Akhmad; Annaastasia, Nurhuda; Risfandi (Jurnal Sosial Ekonomi Perikanan, 2023)
The demand for exports from several Asian countries makes fishery commodities a superior product that is able to provide profits to help the national economy. Southeast Sulawesi has an Ocean Fishing Port (OFP) as the center of an integrated fishing industry in the eastern part of Indonesia that is able to increase fisheries production and is an inter-island trade route. This study aims to determine the feasibility of fish export business at PT. Hui Mei Wei Aquatic Product Trading in Kendari City, Southeast Sulawesi. This research was conducted in June 2022. The research method used is a case study. Research data is collected in the form of total costs (fixed costs and variable costs), production amount, selling prices of fish, and receipts. The data was analyzed using the business feasibility formula, namely the R/C Ratio. The results of this study showed that the R/C Ratio was 1.68. This means that every expenditure of Rp1 by the industry will get revenue of Rp1.68. thus, the fish export business carried out by PT.  PT. Hui Mei Wei Aquatic Product Trading is worthy of development.